Are patients in western Turkey contented with healthcare services? A quality assessment study - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2006)
The purpose of this study was to describe service quality as perceived by 1200 patients who had inpatient treatment at 3 hospitals in Istanbul: university, social security administration, and government. Patients were most satisfied with the helpful attitudes of personnel during check-in procedures, promptness and skill of nurses, overall service provided by physicians, speedy and skilled work of personnel in laboratories and X-ray rooms, and hospitals in general.
Keywords: NURSING-CARE; SATISFACTION